Assessment of Zn and Cu in Primary School Children’s Street Foods - Handayani, Elya Hilda; Oginawati, Katharina; Santoso, Muhayatun (Research of Environmental Science and Engineering, 2020)
Metal elements are needed by body for metabolic processes. For examples are Cu and Zn. These metals present in food naturally. However, food can be contaminated by metals from the environment. Excess consumption of metal elements can cause disease for consumers. Primary school children’s foods are one of the problems of metal contamination that need attention. There are some sellers who put hazardous materials into the food or the food’s sanitation is neglected in food processes. Thus the analysis carried out by first doing sampling at four primary schools in Bandung to check the concentration of Cu and Zn metals in these foods. The number of samples taken is 6 pieces per location. From laboratory analysis using atomic absorption spectrophotometry method the results show the highest Cu concentrations of children’s street foods was Kentang 4,11 mg/kg and the highest of Zn was biting with 22,43 mg/kg.